Color stability of natural colorant on blue pea flowers - Nornabilah, Mohd Hamdan (2010)
The use of natural colorants is highly increasing in the food industry due to strong consumer demand for more natural products. On the other hand, synthetic colorant give harms to consumers that may affect health because of the unsuitable chemicals contained. Color stability of certain product is important to maintain its appearance that differs in many aspects. This study aimed at determining the color stability of blue pea flower based on the storage days, the use of different solvents and its concentrations. The blue pea flower was kept soaked at room temperature with each methanol and ethanol as solvents and an addition of maltodextrin as stabilizer every day for 7 days. Solutions of colors and solvents, methanol and ethanol were then heated at boiling point of each solvent, 64.7°C and 78.4°C, respectively. The samples obtained was analyzed and tested by using a programmed spectrophotometer, giving results of its qualities and changes of the color. Based on the results, methanol with concentration of 20 percent and storage days at the 7th day is at its best in maintaining the color stability. The value of L and a* are quite consistent through the days while b* value undergo little changes that shows its stability compared to other parameters. Thus, the color stability of the blue pea flower based on data collected is suitable to be a natural colorant with a high stability to replace synthetic colorant.